Review in the Policies Entitled for Agricultural Practices in India - Kanta Behera, Shishira; Baig, M A A (International Journal of Psychosocial Rehabilitation, 2025)
The current paper deals with the sole motive to intensify the importance and the effects of various policies that have been created so as to provide boon to the agricultural sector in India. Agricultural policies in India are designed and enforced by a posh system of establishments. States have constitutional responsibility for several aspects of agriculture; however, the central government plays a vital role by developing national approaches to policy and providing the mandatory funds for implementation at the state level. However, no sufficiently sturdy mechanism exists to bring state and central level policy manufacturers along to debate issues, style solutions, and monitor performance. The paper addresses the impressive progress made by the farming sector in the past two decades and the major challenges facing the sector: reduction but ongoing food insecurity and nutrient deficits, a large number of small farms and marginal farms with limited capital, a rising lack of water, low productivity increases and unpredictable consequences of climate change. In this regard, this paper highlights the potential for policy makers to rebalance their priorities from volatile, complex and often overlapping business policies in favor of initiatives that concentrate more broadly on the nutritional needs of poor people and the competitiveness of farmers and rural residents